2004
DOI: 10.1002/meet.1450410119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of task on time spent reading as an implicit measure of interest

Abstract: Information Filtering systems learn user preferences either through explicit or implicit feedback. However, requiring users to explicitly rate items as part of the interface interaction can place a large burden on the user. Implicit feedback removes the burden of explicit user ratings by transparently monitoring user behavior such as time spent reading, mouse movements and scrolling behavior. Previous research has shown that task may have an impact on the effectiveness of some implicit measures. In this work w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Keller et al [21] did not totally assert to [3], they suggest that users spend longer time on a page due to an increase in the complexity of the task. Liu et al [22] supported Keller et al [21] by adding that dwell time alone is only good for measuring factual task but it is not good for intellectual task. They also suggested that that the concept of dwell time should be developed according to the task a user is working on.…”
Section: Related Workmentioning
confidence: 99%
“…Keller et al [21] did not totally assert to [3], they suggest that users spend longer time on a page due to an increase in the complexity of the task. Liu et al [22] supported Keller et al [21] by adding that dwell time alone is only good for measuring factual task but it is not good for intellectual task. They also suggested that that the concept of dwell time should be developed according to the task a user is working on.…”
Section: Related Workmentioning
confidence: 99%
“…For this we sort pages in order of their relevant factors and only the top few pages (based on a threshold, to be taken from the user) are said to be relevant. The activity by the user on the webpage can be inferred by the active time spent by the user, mouse movement and scrolling behaviour on the webpage as indicated in [5] …”
Section: Modifications Proposedmentioning
confidence: 99%
“…Vogt [20] claimed that viewing time normalized by document length is a good predictor of relevance. Kellar et al [8] reported that time spent on reading as measure of user interest becomes more useful as the task becomes more complex. Kelly and Belkin [11] focused on document display time and demonstrated that its usefulness differs significantly according to tasks and users.…”
Section: Related Workmentioning
confidence: 99%
“…Recent researches have investigated common user behaviors and drawn several conclusions on whether implicit feedback is useful for indicating user preference and whether its quality is influenced by tasks or users [8,9,11,22]. They are primarily for Web retrieval on desktops, therefore are not directly applicable for this research.…”
mentioning
confidence: 99%